Incorporating peer-to-peer facilitation with a mid-level fidelity student led simulation experience for undergraduate nurses. (September 2016) - Curtis, Elizabeth; Ryan, Colleen; Roy, Sherre; Simes, Tracey; Lapkin, Samuel; O'Neill, Barbara; Faithfull-Byrne, Annette
Abstract: Background: The aim of this study was to evaluate peer-to-peer facilitated student led mid-level fidelity simulation experiences. Methods: Second and third year nursing students (N = 637) were invited to complete a 16-item 6-point Likert scale questionnaire after the simulation experience. Results: Students reported high self-confidence in their nursing skills (M = 4.14, SD  = 0.92) and a high level of satisfaction in the learning they received during the peer-to-peer facilitated student led simulation experience (M = 4.42, SD = 0.93). Conclusion: Using peer-to-peer teaching strategies during student led simulation experience is an effective approach for ensuring active engagement of all learners during midlevel fidelity group-based simulations and has the potential for broad applicability. Highlights: Peer-to-peer teaching strategies may assist in overcoming barriers to facilitating large cohorts and increase engagement. Students reported high satisfaction and self-confidence after exposure to mid-level fidelity student led simulation experience (SLSE). Mid-level fidelity equipment is a cost effective and can result in high levels of student satisfaction and self-confidence.